2019
DOI: 10.1016/j.dcn.2019.100666
|View full text |Cite
|
Sign up to set email alerts
|

Altered development of hippocampus-dependent associative learning following early-life adversity

Abstract: Highlights Childhood violence is related to hippocampus-dependent learning difficulties. Learning difficulties among children exposed to violence worsen with age. Hippocampal and fronto-parietal cortical function underlie learning difficulties. Learning difficulties specifically in the presence of threat do not change with age. Intraparietal sulcus function underlies threat-specific learning difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 83 publications
(119 reference statements)
1
30
0
1
Order By: Relevance
“…Our findings suggest that violence exposure is negatively associated with associative memory in early childhood, even after accounting for variation in cognitive stimulation and the quality of the physical environment. These findings are in line with prior work documenting poor associative learning among older children, adolescents, and adults exposed to violence (Hanson et al, 2017; Lambert et al, 2019) and extend these findings by demonstrating these associations are present in early childhood, in children far younger than previously examined to assess the impact of violence exposure on memory. Associative learning of two previously unassociated stimuli depends on the hippocampus and other medial temporal lobe structures including the parahippocampal cortex (Eichenbaum and Bunsey, 1995; Yoon et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings suggest that violence exposure is negatively associated with associative memory in early childhood, even after accounting for variation in cognitive stimulation and the quality of the physical environment. These findings are in line with prior work documenting poor associative learning among older children, adolescents, and adults exposed to violence (Hanson et al, 2017; Lambert et al, 2019) and extend these findings by demonstrating these associations are present in early childhood, in children far younger than previously examined to assess the impact of violence exposure on memory. Associative learning of two previously unassociated stimuli depends on the hippocampus and other medial temporal lobe structures including the parahippocampal cortex (Eichenbaum and Bunsey, 1995; Yoon et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…It is possible that these differences contributed to the distinct associations seen. However, given that other studies have found similar associations between violence exposure and memory for real world objects (Lambert et al, 2019), it seems unlikely that these stimuli differences are driving our effects. Still, future work should structure three tasks (associative memory, cued attention, and memory-guided attention) using the same stimulus sets to rule out this possibility.…”
Section: Discussionmentioning
confidence: 57%
“…Reduced hippocampal recruitment during memory encoding has been observed in children exposed to violence in both existing studies (100%), which involved encoding faces paired with other stimuli (Lambert et al 2017b(Lambert et al , 2019.…”
Section: Hippocampal Activationmentioning
confidence: 90%
“… 16 However, when this support is non-existent or inadequate, a failure of the body's functions to return to basal level primarily impacts the cardiovascular and neurological systems, with consequent irreversible loss of connections in the infant brain, due to toxic stress. 17 , 18…”
Section: Discussionmentioning
confidence: 99%